Improved running economy after 20 days of moderate simulated altitude exposure - Saunders, P.; Telford, R.; Cunningham, R.; Pyne, D.; Gore, C.; Hahn, A. A.; Hawley, J. (Journal of Science and Medicine in Sport, 2003)
To investigate the effect of altitude exposure on running economy (RE), 22 highly-trained distance runners (mean VO2max 72.8 ± 4.4 ml.min-1.kg-1; training volume 125 ± 27 km.wk-1) were assigned to three groups; live-high train-low (LHTL) at simulated altitude (2000-3200 m), live-moderate train-moderate (LMTM) at moderate altitude (1570-2000 m) or live-low train-low (LLTL) at normal altitude (600 m) for 20 days. RE was assessed during 4 min periods of running at three sub-maximal speeds (14, 16 and 18 km.h-1) prior to and at completion of each intervention. Measures taken during the final minute of each running speed included oxygen consumption (VO2), ventilation (VE), respiratory exchange ratio (RER), stride rate (SR), heart rate (HR), haemoglobin mass (Hbmass) and concentration of blood lactate (La). VO2 (L.min-1) averaged across the three running speeds was 3.3% lower (p=0.005), after the LHTL intervention compared with the other two groups, indicating improved RE.VE, RER, HR, Hbmass and SR were essentially unchanged after the three interventions. Although not significant (p=0.12), log of La decreased by 24% after the LHTL intervention suggesting, but not proving, that the lower aerobic cost of running was not due to an increased anaerobic component. These results demonstrate that 20 days LHTL but not LMTM improved RE in highly trained distance runners. The improved RE is likely beneficial to performance in endurance events, although the change in RE could not be explained simply by a reduced energy cost associated with VE nor by preferential use of carbohydrate as metabolic substrate.